Jewish education in post-war Legnica as a component of ethnic policy of the ‘People’s Poland’ - Szczepański, Andrzej (Szkolnictwo żydowskie w powojennej Legnicy jako element polityki etnicznej Polski Ludowej, 2022)
Ethnic policy pursued in Poland i.e. in the years 1944 –1989 was characterized by the lack of a uniform approach to dealing with non-Polish residents of the state. Although its main objective was to create a nationally homogeneous society, ethnic fragmentation of the country was allowed at selected times, granting certain privileges to national minorities. Consequently, their education, which is an immanent part of the aforementioned policy, was also subject to significant modifications, among others, in organizational, ideological and programme terms. The overriding objective of the article was to attempt to characterize education of Jewish minority in Legnica, in ethnic policy terms of the ‘People’s Poland’, including educational policy.
Zeszyty Naukowe Collegium Witelona, nr 44(3)/2022, s. 55-71
Keywords: ethnic policy; Jewish minority; the People’s Poland; education of national minorities; Legnica